Machine structural member and its manufacturing method
The method of quenching, tempering, and induction hardening with controlled hardness variations addresses the accuracy and productivity issues in mechanical structural members, achieving high precision and reduced tool wear.
Patent Information
- Application Number
- JP2024520383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-04-26
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2043-04-26
AI Technical Summary
Existing methods for manufacturing mechanical structural members, such as ball screw shafts, fail to achieve desired processing accuracy and increase complexity and time, leading to decreased productivity and tool wear due to variations in hardness and structure.
A manufacturing method involving quenching and tempering to create a sorbite structure with controlled Rockwell hardness variations, followed by plastic working and induction hardening to form grooves and teeth, without annealing, ensuring uniform martensitic and sorbite structures.
This method results in high-precision mechanical structural members with reduced tool wear and improved productivity by maintaining consistent hardness and structure, enhancing thread accuracy and reducing manufacturing costs.
Smart Images

Figure 0007613795000007 
Figure 0007613795000008 
Figure 0007613795000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a machine structural member requiring high precision and a manufacturing method thereof. [Background technology]
[0002] Generally, when steel is processed to manufacture products, the steel is subjected to heat treatment (hardening and tempering) to improve its machinability, grindability, toughness, wear resistance, etc. In addition, heat treatment such as annealing is performed as necessary to improve machinability and processability. The reason for this, as is already well known, is that when processing round bar material having a relatively uniform shape, it is difficult to make the hardness and structure uniform even if quenching and tempering (thermal refining) are performed under general heat treatment conditions.
[0003] Recently, in response to demands for even higher performance in precision machinery and the like, studies are being conducted to improve the accuracy and performance in the field of steel products such as ball screw shafts, screw shafts, gears, etc. In particular, since the method of machining a screw groove by rolling has excellent productivity and can reduce manufacturing costs, there is an increasing demand for a manufacturing method that can obtain a screw shaft with excellent dimensional accuracy using rolling processing.
[0004] For example, Patent Document 1 proposes a manufacturing method for a ball screw shaft in which a screw groove is formed by rolling. The manufacturing method described in Patent Document 1 involves tempering a round bar material to a hardness of HRC25 to HRC35, annealing its outer circumferential surface to HRC23 or less, forming a screw groove by rolling, and hardening the surface of this groove by induction hardening. It is described that this makes it possible to manufacture a ball screw shaft with little bending after heat treatment, lead error of the screw groove, and pitch error without reducing workability.
[0005] Patent Document 2 discloses a method for manufacturing a screw shaft in which a screw groove is rolled on the outer peripheral surface of a normalized steel material and the surface is then subjected to nitriding or sulfur-nitriding. Patent Document 2 describes that a surface-hardened layer can be formed on the surface of the screw shaft without quenching, which involves high-temperature heating, rapid cooling, and transformation, and therefore the precision, quality, and durability of ball screws and sliding screws can be improved. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2003-119518 [Patent Document 2] Japanese Patent Publication No. 2013-92212 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in recent years, there has been a demand for even greater improvement in dimensional accuracy, and even if the manufacturing methods described in Patent Documents 1 and 2 are used, it is sometimes impossible to obtain the desired processing accuracy. Furthermore, when the annealing process described in Patent Document 1 or the nitriding process or sulfur-nitriding process described in Patent Document 2 is carried out, the manufacturing process becomes complicated, and the number of steps and processing time increase, resulting in reduced productivity.
[0008] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a machine structural member having high precision and excellent quality. Another object of the present invention is to provide a method for manufacturing a mechanical structural component that is highly productive, suppresses tool wear during manufacturing, and can produce mechanical structural components with high precision and excellent quality. [Means for solving the problem]
[0009] The above object of the present invention can be achieved by the following configuration [1] or [2]. [1] In mechanical structural components in which grooves and teeth are formed by plastic processing, a hardened layer having a martensite structure formed on the surface by induction hardening; a core region having a sorbite structure; A boundary layer having a mixture of a sorbite structure and a martensite structure formed between the core region and the hardened layer, A machine structural member, characterized in that the core region has a Rockwell hardness of 13 to 28 (HRC), and the variation in the Rockwell hardness is within 6 (HRC). [2] A method for manufacturing the mechanical structural member according to the above [1], A tempering process of tempering a steel material to obtain a tempered material having a sorbite structure, a Rockwell hardness of 13 to 28 (HRC) in a material portion excluding a predetermined thickness from the surface, and a variation in the Rockwell hardness of the material portion within 6 (HRC); a plastic processing step of performing plastic processing on a surface of the tempered material on which the grooves and teeth are formed to obtain a processed material; a high-frequency hardening step of performing high-frequency hardening on the processed material; A manufacturing method for a machine structural member, comprising: Effect of the Invention
[0010] According to the present invention, it is possible to provide a machine structural member having high precision and excellent quality. Furthermore, according to the present invention, it is possible to provide a manufacturing method for a machine structural member, which can suppress wear of tools during manufacturing and manufacture machine structural members with high precision and excellent quality. [Brief description of the drawings]
[0011] [Figure 1] 1(a) to (c) are schematic diagrams showing changes in a steel material when a ball screw shaft is manufactured by the manufacturing method suggested by Patent Document 1. [Diagram 2]2(a) to (c) are schematic diagrams showing changes in a steel material when a ball screw shaft is manufactured under the heat treatment conditions suggested by Patent Document 1. [Diagram 3] FIG. 3 is a graph showing the relationship between the hardness and the position of the S45C material after thermal refining. [Figure 4] FIG. 4 is a graph showing the relationship between hardness and position of the refined material in this embodiment, where the vertical axis represents hardness and the horizontal axis represents the position of the surface layer in a cross section perpendicular to the longitudinal direction of the refined material. [Diagram 5] FIG. 5(a) is a schematic cross-sectional view showing a test material for explaining the hardness measurement positions in this embodiment, and (b) is a side view thereof. [Figure 6] FIG. 6(a) is a cross-sectional view showing a ball screw shaft for explaining the hardness measurement positions, and (b) is its side view. [Figure 7] FIG. 7 is a schematic diagram showing the quenching and tempering conditions of the examples of the invention. [Figure 8] FIG. 8 is a schematic diagram showing the quenching and tempering conditions of the comparative example. [Figure 9] FIG. 9 is a photomicrograph showing the metal structure of a cross section parallel to the shaft of ball screw shaft No. 1 after induction hardening. [Figure 10] FIG. 10 is a photomicrograph showing the metal structure of a cross section perpendicular to the shaft of ball screw shaft No. 1 after induction hardening. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present inventors have carried out various investigations into a machine structural member and a manufacturing method thereof that can improve the machining accuracy, while considering conventional manufacturing methods. According to Patent Document 1, if the surface is annealed (softened) while leaving the refined portion, it is possible to improve the thread precision even after rolling and induction hardening. In other words, Patent Document 1 suggests carrying out (A-1) hardening and (A-2) tempering (refining), (B) annealing, and (C) induction hardening.
[0013] Hereinafter, the state of the structure when a ball screw shaft is manufactured based on the composition of S55C steel material described in JIS G4051:2016 (carbon steel material for machine structure) using the manufacturing method suggested in the above Patent Document 1 will be described. Note that the main composition of S55C steel material is C: 0.52 to 0.58 (mass%), and assuming that the contents of Si, Mn, P and S are also equivalent to those described in JIS G4051, the heat treatment conditions of this steel material are, for example, as follows.
[0014] (A-1) Quenching: 800~850℃ Water cooling Hardness (Rockwell C scale hardness): HRC 60~ (A-2) Tempering: 550~650℃ Rapid cooling Hardness: HRC 30 (B) Annealing: 790℃ Furnace cooling Hardness HRC 0~8.5 Incidentally, (B) hardness after annealing, HRC 0 to 8.5, is a conversion value from Brinell hardness 149 to 192 HB.
[0015] Here, the changes in the steel material through steps (A-1), (A-2) and (B) will be described in more detail with reference to the drawings. 1(a) to (c) are schematic diagrams showing changes in a steel material when a ball screw shaft is manufactured by the manufacturing method suggested in Patent Document 1. Also, Figs. 2(a) to (c) are schematic diagrams showing changes in a steel material when a ball screw shaft is manufactured under the heat treatment conditions suggested in Patent Document 1.
[0016] (A-1) In hardening, the round bar material is heated to the A3 transformation point +30 to 50°C to turn it into γ iron (gamma iron: austenitic face-centered cubic crystal), and then rapidly cooled (hardened) to turn it into martensite (body-centered cubic crystal (tetragonal)), which is a very hard and brittle structure. (A-2) In tempering, the extremely hard and brittle martensite structure is heated to the tempering temperature and then cooled, resulting in a slight decrease in hardness and toughness. As shown in FIG. 1(a), the round bar 1 is tempered by the above steps (A-1) and (A-2), and a tempered portion 11 in which the hardness of the entire material is set in the range of HRC25 to 35 is formed.
[0017] (B) In annealing, the tempered steel is kept in the austenitic structure (790°C) for a sufficient period of time, and then slowly cooled in a furnace. As a result, a softened layer 12 with a hardness of HRC23 or less is formed on the surface, as shown in Figure 1(b). Then, after performing peeling, centerless grinding, and rolling, the surface is induction hardened to form a hardened layer 13 hardened to a range of HRC55 to 62, as shown in FIG. 1(c).
[0018] Generally, the purpose of annealing is to remove internal residual stress caused by processing, soften the structure, and improve ductility. That is, annealing reduces lattice defects in the metal structure and causes recrystallization, which reduces residual stress and softens the material.
[0019] Therefore, if a screw shaft is manufactured using the conventional annealing heat treatment temperature and the above-mentioned conventional manufacturing method, it is possible that the thermally refined portion 11 will not actually remain. Specifically, as shown in Fig. 2(a), the round bar 2 is tempered by quenching and tempering to form a tempered portion 11, but as shown in Fig. 2(b), annealing results in a softened layer 12 extending to the radial center of the round bar 1. This annealing is performed at a high temperature, so the hardness drops to, for example, 0 to 9 (HRC). Then, after peeling, centerless grinding, and rolling, the surface is induction hardened to form a hardened layer 13 hardened by induction hardening on the outermost surface, as shown in Fig. 2(c), and a hardened layer 14 by induction hardening is further formed between the softened layer 12 and the surface hardened layer 13. The present inventors came to the conclusion that when the above-mentioned conventional manufacturing method is carried out under typical heat treatment conditions, a softened layer 12 is present in the center of the screw shaft, and this softened layer 12 becomes a distortion of the screw shaft during the rolling and high-frequency hardening processes, causing a decrease in dimensional accuracy.
[0020] Therefore, the present inventors have conducted further intensive research into a manufacturing method for a ball screw shaft that can suppress deformation and has high precision and excellent quality. First, the present inventors have investigated the cause of the decrease in dimensional accuracy when a ball screw shaft is manufactured using a polished bar (coil to bar) obtained from a steel manufacturer.
[0021] When obtaining a polished bar, the hardness of the polished bar is generally specified by specifying a portion of the screw material and instructing the steel manufacturer on the hardness of the polished bar. However, the polished bar is hardened on the surface layer side, and the hardness decreases as it approaches the core. Therefore, while the surface of the polished bar has the specified hardness, the hardness of the core is unknown, and the polished bar in the obtained state could not obtain the required precision.
[0022] Fig. 3 is a graph showing the relationship between hardness and position of S45C material (manufactured by Nippon Steel Corporation) that was subjected to coil drawing and then tempered. The diameter of the measured S45C material was 16 mm. In the graph shown in Fig. 3, one end of the diameter in a cross section perpendicular to the longitudinal direction of the S45C material is set to 0 mm, and the other end is set to 16 mm. In this specification, the longitudinal direction of a screw, a screw material, a tempered material, etc. refers to the direction in which the screw shaft extends. The hardness of the S45C material that had been tempered after being drawn into the coil was measured. As a result, in the material portion excluding a region of a certain thickness (e.g., 3 mm) from the surface, the surface portion represented by positions of 3 mm and 13 mm in FIG. 3 was compared with the core portion represented by the range of 6 mm to 10 mm, and the core portion showed a value that was about 12 (HRC) lower, forming a graph that forms a U-shape.
[0023] In this way, if the hardness is specified, the hardness of the S45C tempered material obtained is generally recognized to be within the specified range, but in reality there is a large difference in hardness between the surface and core.
[0024] This type of variation in hardness from location to location also occurs when using other types of steel, such as SAE4150 material specified by the Society of Automotive Engineers (SAE) (equivalent to SCM445 in JIS G4053:2016 (alloy steel for mechanical structures)). When SAE4150 material is used and hardened by heating at 850°C for 120 minutes and cooling, and then tempered by heating at 650°C for 300 minutes and cooling, a maximum variation of about 4 (HRC) occurs when comparing the hardness between the center and a position 0.5r (1 / 2 the radius r) away from the center in a cross section perpendicular to the longitudinal direction. In addition, when the SAE4150 material is long, there is also variation in the longitudinal direction (axial direction). For example, when the variation in the cross section perpendicular to the longitudinal direction is 4 HRC, the variation in hardness within a single SAE4150 material can reach 12 HRC.
[0025] Furthermore, for polished bars (Coil to Bar) obtained from steel manufacturers, there is a process in which the coil material is returned to a straight bar material at the steel manufacturer, and this process causes variations in hardness. That is, in the process of gradually processing the coiled material into a linear shape using rollers, there are parts that are stretched and compressed in order to straighten the material, which has twists and bends, and this causes variations in hardness. The inventors of the present application discovered that when thread rolling was actually performed using a material having the above-mentioned hardness variations and the accuracy of the tooth profile, tooth trace and thread pitch was measured, errors occurred in the gear testing machine, making the measurement difficult.
[0026] Specifically, when a ball screw shaft having 20 grooves in the longitudinal direction is manufactured using the above-mentioned tempering method with SAE4150 material, excluding one groove on each end, the cumulative pitch error calculated by adding up the difference in pitch between adjacent grooves for 18 grooves is 16 μm (0.016 mm), which is a large error.
[0027] The above data showing a cumulative pitch error of 16μm (0.016mm) is for when 550 steel materials are stored in the batch furnace. If the number of steel materials in the batch furnace is increased to 1400, the variation will increase further, the hardness will exceed 7 (HRC), the cumulative pitch error will exceed 30μm, and the accuracy will decrease significantly. In this way, if the pitch variation becomes large, peeling occurs on the raceway surface (raceway surface) of the groove in which the balls roll, and if the direction of rotation changes, it becomes easier for operation to become uneven. Note that the cumulative pitch error of the lead after rolling is the same if the high-frequency correction in the next process is excluded.
[0028] The lead accuracy of ball screws is regulated by JIS B1192-3:2018. For example, if the screw accuracy grade is Ct10, the allowable variation (ν 300 ) is 210μm, so when the effective thread length is 72mm, the allowable displacement is 50.4μm. However, for example, if the target value for the thread accuracy grade is between Ct7 and Ct8, the allowable value of the variation (ν 300 ) is approximately 75 μm, so when the effective thread length is 72 mm, the allowable displacement is 18 μm. In other words, the cumulative pitch error when 1,400 steel materials are placed in a batch furnace is within the standard if the grade is Ct10, but if an attempt is made to manufacture a ball screw shaft with even higher accuracy, it will not be within the standard. Therefore, there is a growing demand for a manufacturing method of a ball screw shaft that can further reduce the cumulative pitch error. Furthermore, when the grooves of the ball screw shaft are machined by through-feed rolling, the yield rate is as low as about 60%, lowering productivity. Therefore, there is an increasing demand for a manufacturing method using in-feed rolling, which can stably manufacture machine structural components at low cost.
[0029] Therefore, the present inventors considered that if the variations in metal structure and hardness could be significantly reduced in steel before plastic processing, particularly before rolling processing, it would be possible to improve processing accuracy, and investigated the tempering conditions of the steel.
[0030] For example, even if steel is heated at a general quenching temperature, cooling starts from the surface, so the hardness of the core is significantly lower and the hardness of the surface is higher. Furthermore, if the steel is cooled without being heated to the core, the difference in hardness between the core and the surface becomes even more significant. On the other hand, if the tempering temperature is increased to, for example, 570° C. in order to reduce the hardness of the surface, the hardness of the core is further reduced, making it difficult to uniformize the hardness and structure.
[0031] As a result of the above-mentioned investigations, the inventors have found that by selecting conditions under which the hardness variation in the steel material after quenching is small and a uniform martensite structure is formed, and by determining a target value for hardness after tempering and deciding the tempering temperature, it is possible to obtain high-precision mechanical structural components. The present invention was made based on these findings.
[0032] Hereinafter, the embodiments of the present invention will be described in detail. Note that the present invention is not limited to the embodiments described below, and can be modified and implemented as desired without departing from the gist of the present invention.
[0033] [Method of manufacturing machine structural components] This embodiment is a manufacturing method for manufacturing a machine structural member described later, and includes a tempering process for tempering a material steel to obtain a tempered material having predetermined characteristics, a surface removing process for removing a predetermined thickness from the surface of the tempered material to obtain a raw material, a plastic processing process for performing plastic processing on the surface of the raw material on which grooves and teeth are formed to obtain a processed material, and a high-frequency hardening process for performing high-frequency hardening on the processed material. Note that neither annealing nor annealing is performed between the tempering process and the plastic processing process.
[0034] Hereinafter, as a first embodiment, a manufacturing method for a machine structural member will be specifically described, and as a second embodiment, a manufacturing method for manufacturing a ball screw shaft among machine structural members will be more specifically described.
[0035] <First embodiment> (Refining process) The tempering process is a process in which a steel material is tempered to obtain a tempered material having a sorbite structure, a Rockwell hardness of 13 to 28 (HRC) in the material part excluding a specified thickness from the surface, and a variation in Rockwell hardness in the material part within 6 (HRC). The thermal refining process generally refers to a quenching process and a tempering process, and is a process that can adjust the hardness of the material steel.
[0036] In this specification, the term "Rockwell hardness" refers to a value measured in accordance with the Vickers hardness test described in JIS Z 2244:2009 and converted.
[0037] In the present embodiment, in the quenching process, the material steel is heated to a predetermined temperature, held at that temperature, and then cooled. It is preferable to select the heating temperature and holding time in the quenching process under conditions such that the structure of the material steel after the quenching process becomes a uniform martensite single-phase structure and the crystal grains do not become coarse.
[0038] A uniform martensite single phase structure means that the grain size of the structure is uniform from the surface to the center, and the austenite structure is completely transformed into martensite, rather than a mixed structure of ferrite, martensite, etc. However, when the structure is quantitatively measured using a scanning electron microscope, a transmission electron microscope, an X-ray diffraction method, etc., it is not necessarily required that the martensite structure alone accounts for 100% by area, and ferrite, etc. may remain as an unavoidable impurity. By confirming this, it can be determined that the temperature inside the furnace is uniform during quenching, the temperature rises to the center of the material steel, and the material steel becomes completely austenitic.
[0039] The conditions such as the temperature and time during quenching to keep the variation in the structure and hardness of the steel material after quenching within the above ranges vary depending on the composition of the steel material used and the type of furnace. For example, the quenching temperature can be set to a temperature equal to or higher than the A3 transformation temperature depending on the carbon content based on the phase diagram of the steel, and the steel material can be made into a completely austenitic single-phase structure by heating the workpiece to its center sufficiently.
[0040] If the steel material is completely converted into an austenitic structure and then rapidly cooled, the martensitic transformation can be sufficiently promoted. The cooling method is not particularly limited, but cooling with water (water cooling), cooling with oil (oil cooling), etc. can be used. Oil cooling suppresses the formation of coarsened martensite structures, and can prevent the test material from becoming brittle after quenching and the occurrence of quench cracks. On the other hand, if the steel is cooled with water, many bubbles of water vapor will adhere to the surface of the steel material after quenching, and the insulating effect of these bubbles will prevent the steel from being cooled rapidly, which can result in variations in hardness. Therefore, it is preferable to use oil cooling.
[0041] If the martensitic transformation has not progressed sufficiently after cooling, a method of further maintaining the low temperature by subzero treatment or the like after quenching to advance the martensitic transformation can be adopted. However, since this complicates the cooling equipment and process and increases the manufacturing cost, it is preferable to advance the martensitic transformation by a normal cooling method. In particular, in this embodiment, since reducing the variation in Rockwell hardness in the material portion of the material steel after quenching is also an important factor, it is preferable to select oil cooling, which is less likely to cause variation in hardness.
[0042] As another condition for the quenching process, if the number of quenching processes performed at one time increases, it generally becomes difficult to uniformize the quenching temperature and cooling conditions, so it is preferable to adjust the number of quenching processes as well.
[0043] As a specific method for determining the conditions (heating temperature and heating time) of the quenching process, a quenching test process is performed in which a test material having substantially the same shape and composition as the steel material to be used is used and the test material is quenched under various conditions. That is, in the quenching test process, before the thermal refining process, the structure of the test material quenched under various conditions is observed, whether the structure of the test material is a uniform martensite single phase structure is confirmed, and the quenching heating conditions that result in a uniform martensite single phase structure are selected. In this embodiment, as described later, the conditions of the tempering process are selected so that the Rockwell hardness and variation of the material part after the tempering process are within the desired range. However, in order to set the hardness and variation to the desired range after the tempering process, it is preferable to measure the variation of the Rockwell hardness of the material part even after the quenching process and select the quenching heating conditions that bring the variation to within 6 (HRC).
[0044] After the quenching process, as described above, a tempering process is carried out to convert the obtained tempered material into a sorbite structure (including a uniform microstructure equivalent to sorbite), which is a uniform microstructure. The tempered material with the sorbite structure has the ductility and mechanical strength required for plastic processing, so that the tempering process can improve the processing accuracy.
[0045] Furthermore, this tempering process makes the Rockwell hardness of the material portion 13 to 28 (HRC), and the variation in Rockwell hardness of the material portion 13 to 28 (HRC) is kept within 6 (HRC). If the Rockwell hardness of the material obtained by the tempering process is less than 13 HRC, plastic processing becomes difficult. On the other hand, if the Rockwell hardness of the material exceeds 28 HRC, the surface of the material after surface removal becomes hard, and although processing is possible, the life of the die tool is significantly reduced. Furthermore, if the variation in Rockwell hardness exceeds 6 HRC, the thread processing accuracy decreases. Therefore, the tempering process is carried out so that the Rockwell hardness of the material portion in the tempered material after the tempering process is 13 to 28 (HRC) with a variation of 6 (HRC) or less.
[0046] In order to control the Rockwell hardness and its variation of the material part by tempering as described above, it is preferable that the heating temperature in the tempering process is adjusted based on a graph of tempering temperature and hardness specific to the material steel used. A publicly known graph of tempering temperature and hardness specific to the material steel may be obtained, or a graph may be created by tempering the material steel used at various temperatures and measuring the hardness thereafter.
[0047] As with the method for determining the conditions for the quenching process, a specific method for determining the heating conditions for the tempering process includes using a test material after quenching and subjecting the test material to tempering under various conditions. That is, in the tempering test process, the structure of the test material tempered under various conditions is observed and the hardness variation is measured. Then, the tempering heating conditions are selected such that the test material has a sorbite structure, the Rockwell hardness of the material part is 13 to 28 (HRC), and the variation in Rockwell hardness of the material part is within 6 (HRC). In this way, the actual tempering process can be performed using the tempering heating conditions selected in the tempering test process. The Rockwell hardness of the material of the test material is preferably 20 to 26 (HRC). The variation in Rockwell hardness is preferably within 2 (HRC), and more preferably within 1 (HRC).
[0048] The hardness variation after the tempering test process is preferably measured at any number of different measurement points in the core region, and if the difference between the maximum and minimum Rockwell hardness values at these measurement points is within 6 (HRC), the hardness variation can be considered to be within 6 (HRC).
[0049] Depending on the type of steel material, the hardness after quenching may affect the hardness after tempering. Therefore, it is preferable not only to determine the tempering temperature based on a graph of tempering temperature and hardness, but also to determine the final tempering heating conditions taking into consideration the measurement results of a hardness test of the test material after quenching. Although details will be described later, the hardness after quenching varies depending on the amount of carbon contained in the steel material. Therefore, if the hardness after quenching is equal to or greater than the critical hardness, it can be determined that the minimum level of quenching has been performed.
[0050] For example, if the measurement result of the hardness of the core of the test material after the quenching test is equal to or higher than the critical hardness but is low, the hardness of the test material after the tempering test may be lower than the desired range. Therefore, it is preferable to set the tempering temperature lower than the temperature derived from the graph and set the tempering heating conditions so that the hardness of the tempered material after tempering is high. On the other hand, if the hardness measurement result of the test material after the quenching test is hard throughout the material, the hardness of the test material after the tempering test may be higher than the desired range. Therefore, it is preferable to set the tempering temperature higher than the temperature derived from the graph and set the tempering heating conditions so that the hardness of the tempered material after tempering decreases.
[0051] However, if the measurement result of the hardness of the core is lower than the critical hardness, it is assumed that the hardening has not been performed to the core of the material steel (the heating temperature has not reached the core) or the temperature inside the furnace is uneven. Therefore, it is preferable to review the heating conditions, such as increasing the heating temperature during hardening or lengthening the soaking period.
[0052] Furthermore, the measurement of hardness and observation of the structure of the test material after the quenching test can be omitted. In this case, it is preferable to carry out a tempering test process in which quenching is carried out using a tempered test material having substantially the same shape and composition as the material steel before the quenching process, and then tempering the tempered test material after quenching at a heating temperature selected based on the relationship between the tempering temperature and hardness specific to the material steel. This tempering test process is a process for selecting the quenching heating conditions and tempering heating conditions so that the structure of the tempered test material after tempering becomes a sorbite structure, and the Rockwell hardness of the material part is 13 to 28 (HRC) with a Rockwell hardness variation of within 6 (HRC). Therefore, it is preferable that the actual quenching process is performed using the quenching heating conditions selected in the thermal refining test process, and the tempering process is performed using the tempering heating conditions selected in the thermal refining test process.
[0053] In the tempering test process, if a sorbite structure is not formed as a result of tempering the tempered test material after quenching, there is a possibility that the martensitic transformation was not complete after quenching, so for example, the heating conditions and cooling conditions of the quenching process should be reviewed. Furthermore, if the hardness or its variation is not within the desired range, it is possible that the quenching and tempering temperatures are inappropriate or that quenching has not been completely achieved to the core, so the heating conditions, etc. of the quenching and tempering processes should be reviewed.
[0054] (Surface removal process) After the above-mentioned tempering process, the hardness of the tempered material increases rapidly from a certain position toward the surface. Therefore, generally, when forming grooves and teeth of a machine structural member by plastic processing, a predetermined thickness is removed (cut and grind) from the surface of the tempered material to obtain a raw material, and then the plastic processing is performed. As a result of this plastic processing, the surface shape of the tempered material viewed from the side has multiple grooves and teeth between each groove. Here, the thickness to be removed when S45C material is selected as the material steel will be explained below.
[0055] Fig. 4 is a graph showing the relationship between the hardness and the position of the tempered material in this embodiment, where the vertical axis is hardness and the horizontal axis is the position of the surface layer in a cross section perpendicular to the longitudinal direction of the tempered material. In Fig. 4, the hardness is measured up to the vicinity of the surface. The tempered material shown in Fig. 4 is a material that is heated at 890°C in the quenching process, heated uniformly in the furnace for 30 minutes, and then heated at 500°C in the tempering process for 120 minutes, and then cooled, thereby obtaining a sorbite structure.
[0056] As shown in FIG. 4, the hardness of the tempered material increases rapidly from a depth of about 1.0 mm from the surface toward the surface. Therefore, in this embodiment, after the tempering process, the region from the surface to a predetermined thickness, i.e., the region including at least the part where the hardness of the tempered material increases sharply, is removed. In this embodiment, for example, a region of 3.0 mm thickness is removed from the surface to obtain a raw material. As a result, the hardness of the entire raw material can be set to 13 to 28 (HRC), and the hardness variation can be kept within 6 (HRC).
[0057] In FIG. 4, the region where the hardness increases rapidly is about 1.0 mm from the surface of the tempered material, so the region to be removed should include at least the region where the hardness increases rapidly (the region from the surface to about 1.0 mm), and it is preferable to remove to a depth of about 2.0 to 3.0 mm from the surface. As shown in FIG. 4, when the surface of the tempered material is removed to a depth of 3.0 mm, the hardness of the material before plastic processing is slightly lower near the center and slightly higher near the surface, but the hardness is approximately uniform in the radial direction of the material.
[0058] In this embodiment, the surface removal step is performed, but this step is not necessarily required. For example, if the structure of the tempered material obtained after the tempering step is a sorbite structure, the Rockwell hardness of the entire tempered material is 13 to 28 (HRC), and the variation in Rockwell hardness is within 6 (HRC), the surface removal step can be omitted. In this case, the yield can be further improved.
[0059] (Plastic working process) In this embodiment, the surface removing step removes the area from the surface to a depth of about 3.0 mm, and a tempered material (raw material) with a diameter of about 10 mm is obtained. Then, the surface of the raw material on which the grooves and teeth are formed is subjected to plastic processing to form grooves and teeth of a desired shape, and a processed material is obtained. The hardness of the screw tooth tip (outer diameter side of the shaft) after plastic processing is about 33 (HRC), and the hardness of the screw tooth root (near the valley bottom) is about 27 (HRC). That is, the area from the tooth root of the screw shaft to a position of 0 to 0.5 mm after plastic processing is hardened by the plastic processing, but the hardness of the raw material part before plastic processing is maintained.
[0060] As described above, when the structure and hardness of the tempered material after tempering are within the desired range and the surface removal step is not performed, the plastic processing step applies plastic processing to the surfaces of the tempered material after tempering that form the grooves and teeth. Even in such a case, the hardness of the thread tooth tip and the thread tooth root after plastic processing will be the same as above, and the hardness of the tempered material before plastic processing will be maintained in the parts other than the area hardened by plastic processing.
[0061] In this embodiment, since the hardness is adjusted to be approximately uniform by the above-mentioned tempering process, and the surface has a hardness suitable for plastic processing, there is no need to perform either annealing or tempering between the tempering process and the plastic processing process.
[0062] (High frequency hardening process) Next, the obtained processed material is subjected to induction hardening. In this embodiment, for example, a ball screw shaft is the subject of the present invention, and the groove of the ball screw shaft is a shaft in which balls roll between the nut and the groove, thereby converting rotational motion into linear motion and linear motion into rotational motion. Therefore, the groove (raceway surface) in which the balls roll is subjected to a large pressure at the contact portion with the balls, and therefore, in order to give hardness to the surface of the groove and prevent peeling due to contact with the balls, it is necessary to transform the surface of the groove into martensitic. In this embodiment, the conditions for induction hardening are not particularly limited, and the conditions are such that the surface has a uniform martensite single phase structure. Through the above steps, the machine structural member according to this embodiment can be obtained.
[0063] According to the manufacturing method of the machine structural member of this embodiment, the material before forming the grooves by plastic processing has a structure and hardness suitable for plastic processing, and the hardness variation from the surface to the deep part is small, within 6 (HRC). Therefore, it is possible to suppress the wear of the tool and the deformation due to the plastic processing, and it is possible to obtain a machine structural member with high precision and excellent quality. Furthermore, according to the manufacturing method of this embodiment, 50% or more of the diameter of the refined material before the surface removal step can be made to have a substantially uniform hardness with little variation, so that when the surface removal step is carried out, the removal depth can be made shallow, improving the yield. Furthermore, in this embodiment, the steel material is tempered so that the hardness range and variation are within a predetermined range, and the ball screw shaft obtained by carrying out the subsequent plastic processing and high-frequency hardening has excellent thread precision. In addition, if annealing and tempering are not carried out, productivity can be improved and manufacturing costs can be reduced. Note that, when carrying out the plastic processing step to form the grooves and teeth, if the hardness and hardness variation of the material are within the above range and the material has a sorbite structure (including a fine uniform structure equivalent to sorbite), a step such as annealing may be carried out between the tempering step and the plastic processing step, and in either case, a ball screw with excellent thread precision can be obtained.
[0064] In addition, in the manufacture of the above-mentioned mechanical structural members, the heat treatment steps before the plastic processing of the steel material, i.e., heat treatment steps such as tempering, normalizing, annealing, and annealing, may be carried out as a series of steps. By carrying out the heat treatment in a series of steps in this way, production efficiency can be improved and manufacturing costs can be reduced. As a result, CO2 emissions can be reduced for the entire manufacturing process including the next process, and therefore the overall manufacturing costs can be reduced.
[0065] As described above, this embodiment is for tempering a steel material for forming grooves by plastic processing, but is particularly suitable for forming grooves by infeed rolling. In-feed rolling requires that the workpiece and the thread are parallel, that the workpiece does not extend in the axial direction, and that the workpiece deforms only in the radial direction in which the thread is formed. According to the manufacturing method of this embodiment, the Rockwell hardness of the material is 13 to 28 (HRC), and the material is tempered to a relatively hard state, so that the workpiece can be prevented from extending in the axial direction during in-feed rolling, and a machine structural member having excellent processing accuracy can be easily obtained. Therefore, when in-feed rolling is performed using the tempered material obtained by the method of this embodiment, the yield can be improved and the manufacturing cost can be reduced.
[0066] <Second embodiment> As the second embodiment, a method for manufacturing a ball screw shaft will be specifically described. In the second embodiment described below, the same parts as those in the first embodiment are denoted by the same names, and detailed descriptions of each process will be omitted.
[0067] (Refining process) As the steel material, an SAE4150 round bar is prepared, and a thermal refining process is carried out using, for example, a continuous furnace. First, a quenching process is carried out. The heating temperature in the quenching process is set to a temperature preferably equal to or higher than the A3 transformation point of about 780°C, based on the carbon content (0.48 to 0.53 mass%) of the SAE4150 material and the phase diagram, more preferably equal to or higher than 830°C, and more preferably lower than 870°C.
[0068] In the above embodiment, the tempering is performed using a continuous furnace, but the type of furnace is not particularly limited. When tempering is performed using a continuous furnace, it is preferable to reduce the open area and heat for a short time in order to prevent cracks caused by the formation of a decarburized layer, since the tempering is performed in the atmosphere. In addition, when a continuous furnace is used, continuous heating can be performed with a direct flame, so that an excellent heat transfer coefficient can be obtained and uneven heating can be suppressed, and compared to the use of a batch furnace, only the required number of material steel materials can be tempered. Therefore, by using a continuous furnace, it is possible to suppress the increase in the number of stocks and to realize a reduction in energy consumption and CO2 emissions. When a continuous furnace is used, the heating holding time is preferably, for example, 15 to 30 minutes. In addition, when the material steel is long, the material steel is arranged horizontally in a river shape to prevent bending of the material steel, thereby shortening the soaking time.
[0069] On the other hand, in a batch furnace, it may be difficult to uniform the temperature inside the furnace depending on the position and number of carbon heaters, and when a large number of steel materials are tempered at once, the variation increases in proportion to the number of steel materials. Such variation tends to increase as the volume of the furnace increases. In addition, when the steel material is long and needs to be tempered while standing in the batch furnace, the heat treatment is likely to become more non-uniform and the variation increases, making it difficult to achieve high precision. However, a batch furnace has the advantage that the atmosphere can be adjusted to a vacuum or an inert gas, which allows stable tempering. Therefore, it is possible to use a batch furnace depending on the size of the steel material and the tempering conditions. However, when using a batch furnace, in order to ensure a uniform heating state, it is preferable to set the soaking time and holding time taking into consideration the placement of the heater, the placement of the workpiece, and the capacity of the furnace, and it is sufficient to set them so that the core is heated to the required specified temperature.
[0070] In this embodiment, the heating conditions in the quenching process are, for example, 840° C. for 20 minutes. Thereafter, oil cooling is performed, whereby the structure and hardness of the material steel after the quenching process can be adjusted to a predetermined range.
[0071] Here, as a specific method for determining the conditions of the quenching process, a quenching test process is performed in which a test material having substantially the same shape and composition as the material steel (SAE4150 material) to be used is used, and quenching is performed under various conditions, as in the first embodiment. Specifically, the structure of the test material quenched under various conditions is observed, and it is confirmed whether or not it is a uniform martensite single phase structure, so that the heating conditions in the actual quenching process can be determined.
[0072] 5(a) is a schematic cross-sectional view of a test material for explaining the measurement positions of hardness in this embodiment, and (b) is a side view thereof. The hardness may be measured at any number of different measurement points, but it is preferable to measure at a number of measurement points where differences in hardness are likely to appear in the material portion excluding a predetermined thickness from the surface. Specifically, the longitudinal length of the test material 21 is L, the cross section perpendicular to the longitudinal direction at a position of 0.1L from one end 21a to the other end 21b of the test material 21 is surface S1, the cross section perpendicular to the longitudinal direction at a position of 0.5L from one end 21a to the other end 21b of the test material 21 is surface S2, and the cross section perpendicular to the longitudinal direction at a position of 0.9L from one end 21a to the other end 21b of the test material 21 is surface S3, and these surfaces S1 to S3 are axial measurement surfaces. 5(a), for example, for surface S1, the center is set as measurement point P0, and the distance from measurement point P0 to a point on the outer circumference is set as radius r. Four measurement points P1, P2, P3, and P4 are selected at approximately equal intervals on the circumference 0.5r away from measurement point P0, and these measurement points P0 to P4 are set as radial measurement positions. Similarly, for surfaces S2 and S3, radial measurement positions represented by measurement points P0 to P4 are set.
[0073] In this embodiment, the hardness variation can be determined by the difference between the maximum and minimum values when comparing the Rockwell hardness at measurement positions within the same plane perpendicular to the longitudinal direction in the core region of the test material 21 and throughout the entire core region. That is, the comparison of Rockwell hardness within the same surface means a comparison of hardness at five radial measurement positions (measurement points P0 to P4) for each surface C. Also, the comparison of Rockwell hardness at measurement positions in the entire core region means a comparison of Rockwell hardness at five radial measurement positions (measurement points P0 to P4) on all three axial measurement surfaces (S1 to S3).
[0074] In this embodiment, it is preferable to select heating conditions that satisfy all of the following conditions (a) to (c) as the heating conditions in the actual quenching process. (a) On each surface, the difference between the maximum and minimum Rockwell hardness values on the same surface (measurement points P0 to P4), i.e., at five locations, is 2 (HRC) or less. (b) The difference between the maximum and minimum Rockwell hardness values at five radial measurement positions (measurement points P0 to P4) on three axial measurement surfaces (surfaces S1 to S3), i.e., 15 positions, is 6 (HRC) or less. (c) The maximum and minimum Rockwell hardness values at five radial measurement positions (measurement points P0-P4) on three axial measurement surfaces (surfaces S1-S3), i.e., 15 positions, are all within the range of 16-26 (HRC). Note that it is preferable that the maximum and minimum Rockwell hardness values are within the range of 16-26 (HRC) after hardening for all test materials, including not only the 15 positions on one piece but also the variation within the furnace and the variation within the lot.
[0075] After the quenching process, a tempering process is carried out. The heating temperature in the tempering process is determined based on a graph showing the tempering temperature and hardness of SAE4150 material. In this embodiment, the heating temperature in the tempering process is determined so that the hardness of the material part of the tempered material after the tempering process is within the range of 13 to 28 (HRC), so in the case of SAE4150 material, the temperature is preferably about 650°C or higher, for example. Also, the upper limit of the tempering temperature is preferably set to a temperature lower than 720°C, which is the A1 transformation point of SAE4150 material.
[0076] However, the relationship between the actual tempering temperature and hardness varies depending on the type of furnace, the season and batch size in which the tempering is performed, the length and shape of the workpiece, etc. Therefore, it is preferable to determine the actual tempering temperature by referring to a graph created under the same conditions as those for the actual tempering, and taking into consideration the hardness of the material steel after quenching. Specifically, a test material for which the quenching heating conditions have been determined is used, and the tempering temperature obtained from the graph is used as a standard, and the tempering is performed by adjusting the temperature higher or lower than this temperature, and the hardness of the material part of the obtained tempered material is measured, so that the optimum tempering temperature can be adjusted, and it is sufficient to adjust it so that the core is heated to the required specified temperature.
[0077] In this embodiment, the tempering conditions are, for example, maintaining the temperature at 700° C. for 60 minutes, followed by cooling. This results in a sorbite structure. Furthermore, if the heating in the quenching and tempering processes is carried out in the atmosphere, the carbon (C) contained in the steel material will react with the oxygen (O2) or water vapor in the atmosphere, causing a decarburized layer to form, which may lead to cracks. Surface decarburization and ferrite decarburization of materials are caused by several factors. Overheating causes the reaction of carbon with oxygen and water vapor in the air from the surface layer of the steel material toward the center, forming a decarburized layer from which carbon has been removed. The decarburized layer is also formed by the atmosphere in the furnace during heat treatment in the tempering process. If rust or black scale (iron oxide) is formed on the surface of the steel material, or if scratches or the like are formed, the oxygen in the iron oxide reacts with carbon to form CO2, which causes decarburization and leads to defects such as cracks. Such decarburization begins earlier when the temperature is close to the quenching temperature. Therefore, the atmosphere during heating in the quenching and tempering processes is preferably an inert atmosphere to prevent the bonding of carbon and oxygen, and is preferably an N2 atmosphere in consideration of costs and the like.
[0078] (Surface removal process) After the above-mentioned tempering process, a region of, for example, 3.0 mm in thickness is removed from the surface of the tempered material to obtain the tempered material (raw material). As a result, the hardness of the raw material obtained by the surface removing process falls within the range of about 18.0 to 23.5 (HRC), as shown in the range of 3.0 to 13.0 mm in Figure 4, and the hardness variation can be about 5.5 (HRC). The thickness to be removed from the surface of the refined material must be appropriately selected depending on the presence or absence of oxide scale and the diameter of the material, and it is preferable to set the thickness to be removed so that the range and variation of hardness after surface removal falls within the above range.
[0079] Furthermore, similarly to the first embodiment, if the structure and hardness of the tempered material obtained by the tempering process are within the desired range, the surface removal process can be omitted, thereby further improving the yield.
[0080] (Plastic working process) Next, without annealing or tempering the material obtained by the surface removal step, grooves and teeth are formed on the peripheral surface of the material by, for example, infeed rolling to obtain a worked material.
[0081] In this embodiment, similarly to the first embodiment, when the surface removing step is not performed, the peripheral surface of the tempered material after tempering may be subjected to plastic processing in the plastic processing step.
[0082] (High frequency hardening process) Next, the obtained processed material is subjected to induction hardening. The conditions of induction hardening are not particularly limited, but for example, conditions such as coil fixed hardening can be used for workpieces with short longitudinal lengths, and coil moving hardening can be used for workpieces with long longitudinal lengths.
[0083] In the manufacturing method of the machine structural member according to the second embodiment, the steel material is also tempered so that the range and variation of hardness are within a predetermined range, so that the ball screw shaft obtained by carrying out the subsequent plastic processing and induction hardening has excellent screw precision. Furthermore, when annealing and tempering are not carried out, the productivity can be improved and the manufacturing cost can be reduced.
[0084] The ball screw shaft obtained by the manufacturing method according to the present embodiment can be used, for example, as a screw shaft for a brake actuator, although the use is not limited thereto.
[0085] The manufacturing method according to the present invention is not limited to the manufacturing method of a ball screw shaft, but can be applied to mechanical structural components of various shapes that require high precision and excellent quality, in which grooves and teeth are formed by plastic processing and then the surfaces of the grooves and teeth are hardened by induction hardening. Examples of mechanical structural members include screw shafts such as ball screw shafts, as well as racks and gears. More specifically, the present invention can be applied as a manufacturing method for ball screws, trapezoidal screw shafts, involute gears, trochoid gears, arc gears, serrations, and the like.
[0086] Next, a machine structural member according to an embodiment of the present invention will be described in detail.
[0087] [Machine structural components] In the machine structural member according to this embodiment, grooves are formed by plastic processing, and teeth are formed between a plurality of grooves adjacent in the longitudinal direction when viewed from the side. In addition, the surfaces of the teeth, i.e., the surfaces of the tooth bottom, flank face and cutting edge, have a hardened layer having a uniform martensite single phase structure formed by induction hardening. Furthermore, the machine structural member has a core region having a sorbite structure, and a boundary layer formed between the core region and the hardened layer, in which the sorbite structure and the martensite structure are mixed. Furthermore, this machine structural member has a sorbite structure, and the Rockwell hardness in the region excluding the hardened layer is 13 to 28 (HRC), and the variation of this Rockwell hardness is within 6 (HRC).
[0088] In this embodiment, the variation in Rockwell hardness is preferably expressed as the difference between the maximum and minimum values when the Rockwell hardness is measured at a number of arbitrary different measurement points in the core region. In other words, the difference between the maximum and minimum values is preferably within 6 (HRC). The Rockwell hardness in the core region can be expressed by the Rockwell hardness at any of a plurality of different measurement points, and it is preferable that both the maximum and minimum values are within the range of 13 to 28 (HRC).
[0089] The Rockwell hardness in the core region is preferably 15 (HRC) or more, more preferably 17 (HRC) or more, and even more preferably 19 (HRC) or more. It is also preferably more than 20 (HRC), more preferably more than 21.5 (HRC), even more preferably 21.9 (HRC) or more, and particularly preferably 22.3 (HRC) or more. The Rockwell hardness in the core region is preferably 26 (HRC) or less, more preferably 25 (HRC) or less, and even more preferably less than 24 (HRC). It is also preferably 23.7 (HRC) or less, and even more preferably 23.5 (HRC) or less.
[0090] When comparing the Rockwell hardness at any of a plurality of different measurement points, the difference between the maximum and minimum values is preferably less than 4 (HRC), more preferably less than 2.5 (HRC), and even more preferably within 2.2 (HRC).Moreover, it is preferably within 2.0 (HRC), more preferably within 1.6 (HRC), and even more preferably within 1.2 (HRC).
[0091] The mechanical structural member according to the present embodiment is obtained by the above-mentioned manufacturing method for a mechanical structural member, and therefore can obtain high precision and excellent quality. Furthermore, in the mechanical structural member according to the present embodiment, the structure of the material before the grooves and teeth are formed by plastic processing is a sorbite structure, and the hardness and its variation are adjusted to a predetermined range. Therefore, even after induction hardening, the core region has a sorbite structure, and the Rockwell hardness and its variation are within the above-mentioned specified range, and in particular, the hardness variation has a characteristic property compared to conventional mechanical structural members.
[0092] Hereinafter, the measurement positions for Rockwell hardness will be described using a ball screw shaft as an example of a machine structural member. FIG. 6(a) is a cross-sectional view showing a ball screw shaft for explaining the hardness measurement positions, and (b) is its side view. As shown in Fig. 6(a) and Fig. 6(b), the ball screw shaft 31 has grooves 32 formed by infeed rolling, whereby teeth 33 are formed between each of the multiple grooves 32 adjacent in the longitudinal direction, and further has a hardened layer 31a formed on the surface by induction hardening. The tempered material before infeed rolling, plastic processing and induction hardening are entirely of a sorbite structure. Then, induction hardening forms the hardened layer 31a having a uniform martensite single phase structure. Therefore, a boundary layer 31c is formed between the core region 31b having the sorbite structure and the hardened layer 31a, in which the sorbite structure changes to the martensite structure as it approaches the hardened layer 31a from the core region 31b.
[0093] In this embodiment, the Rockwell hardness and its variation of the core region 31b are specified. A method for measuring the Rockwell hardness and its variation of the core region 31b will be specifically described below. 6(b), the length in the longitudinal direction of the ball screw shaft 31 is defined as L, and a cross section perpendicular to the longitudinal direction at a position, for example, 0.1L away from one end 31e of the ball screw shaft 31 is defined as a surface S1. Similarly, a cross section (not shown) at a position, for example, 0.5L away from the one end 31e is defined as a surface S2, and a cross section (not shown) at a position, for example, 0.9L away from the one end 31e is defined as a surface S3, and these three surfaces are axial direction measurement surfaces. For S1, the center is set as the measurement point P0, and the distance from the center to a point on the outer circumference of the ball screw shaft 31 is set as the radius r. Four measurement points P1, P2, P3, and P4 are selected at approximately equal intervals on the circumference 0.5r away from the measurement point P0, and these measurement points P0 to P4 are set as the radial measurement positions. Similarly, the radial measurement positions represented by the measurement points P0 to P4 are set for the other two surfaces.
[0094] The hardness variation in this embodiment can be determined by the difference between the maximum and minimum values when comparing the Rockwell hardness at all radial measurement positions in the same plane perpendicular to the longitudinal direction of the ball screw shaft 31 and on all axial measurement surfaces. In other words, in the ball screw shaft 31 of this embodiment, the difference between the maximum and minimum Rockwell hardness values at all radial measurement positions on all axial measurement surfaces is within 6 (HRC), and the Rockwell hardness at all measurement positions is in the range of 13 to 28 (HRC).
[0095] In addition, when the mechanical structural member is a ball screw shaft as shown in FIG. 5, the preferred range of Rockwell hardness at all measurement positions (measurement point P0 to measurement point P4 × surface S1 to surface S3) and the preferred range of variation in Rockwell hardness are the same as in the case of the above-mentioned mechanical structural member.
[0096] In the above embodiment, the cross section at a position 0.1L away from one end 31e of the ball screw shaft 31, the cross section at a position 0.5L away from one end 31e, and the cross section at a position 0.9L away from one end 31e are selected as the axial direction measurement surface, but the present invention is not limited thereto. For example, it is preferable to set one surface at a position selected in a range of 0.05L to 0.20L away from one end 31e in the longitudinal direction of the ball screw shaft 31, one surface at a position selected in a range of 0.45L to 0.55L away from one end 31e, and one surface at a position selected in a range of 0.80L to 0.95L away from one end 31e.
[0097] The mechanical structural member according to the present invention is not limited to the ball screw shaft, but may be a ball screw, a trapezoidal screw shaft, an involute gear, a trochoid gear, a circular gear, a serration, or other various mechanical structural members. In the case of such various shapes, it is preferable to appropriately select the measurement position of the Rockwell hardness according to the shape, and it is more preferable to select a plurality of measurement points where the hardness variation is likely to occur. In any case, the Rockwell hardness in the core region having the sorbite structure is within the range of 13 to 28 (HRC), and the variation of the Rockwell hardness is within 6 (HRC). The preferable range of the Rockwell hardness in the core region and the preferable range of the variation of the Rockwell hardness are as described above. EXAMPLES
[0098] An example of the machine structural member and a manufacturing method thereof according to the present embodiment and a comparative example will be described below.
[0099] [Manufacturing of machine structural components (ball screw shafts) under the conditions of the invention example] (Quenching process) SAE4150 steel material was prepared and quenched in a continuous furnace at the quenching temperature and time described below. In the present invention example, the heating temperature and holding time were set so that the steel material after quenching had a uniform martensite single phase structure. Therefore, the steel material after quenching had a uniform martensite single phase structure.
[0100] (Tempering process) Thereafter, based on a graph showing the relationship between the tempering temperature and hardness of SAE4150 material, the tempering heating temperature and holding time were set so that the Rockwell hardness would be 13 to 28 (HRC).
[0101] As an example, the quenching and tempering conditions of an example of the invention are shown in FIG. In the example of the invention, a continuous furnace was used, and the quenching process involved passing the material through a furnace heated to 840°C for 20 minutes, followed by oil cooling.Then, in the tempering process, the material was heated to 700°C, held there for 60 minutes, and then air-cooled.
[0102] [Evaluation of hardness of tempered material (evaluation of variation at different positions in a continuous furnace)] Tempering was carried out under the conditions of the above-mentioned example of the invention, and one piece of tempered material was taken from each of three locations in the continuous furnace. The Rockwell hardness was measured on the axial measurement surface represented by surface S2 shown in Figure 5, and on the radial measurement positions represented by measurement points P0 to P4. The steel material was placed on a mesh belt and flowed through the continuous furnace, and tempered materials were collected from three locations: the center and both ends (left and right ends) in the direction perpendicular to the direction of travel of the steel material. In this example, the tempered material placed at the left end was called tempered material No. 1-1, the tempered material placed at the center was called tempered material No. 1-2, and the tempered material placed at the right end was called tempered material No. 1-3. The hardness measurement results of tempered materials No. 1-1, 1-2, and 1-3 are shown in Table 1 below.
[0103] [Table 1]
[0104] [Evaluation of hardness of tempered material (evaluation of variation in the longitudinal position of tempered material)] Tempering was carried out under the conditions of the above-mentioned invention example, and a total of three tempered samples were taken from arbitrary positions in the continuous furnace. For each tempered sample, the Rockwell hardness was measured at the axial measurement surfaces represented by the surfaces S1 to S3 shown in Figure 5 and at the radial measurement positions represented by the measurement points P0 to P4. In this example, the three tempered materials were designated as tempered materials No. 1-4, 1-5, and 1-6. The measurement results of the hardness of each tempered material are shown in Tables 2 to 4 below.
[0105] [Table 2]
[0106] [Table 3]
[0107] [Table 4]
[0108] [Manufacturing of mechanical structural components (ball screw shafts) under comparative example conditions] (Quenching process) SAE4150 steel material was prepared and quenched in a batch furnace at the heating temperature and holding time described below. In the comparative example, the structure of the steel material after quenching was not confirmed, and the standard heating temperature and holding time were set.
[0109] (Tempering process) Thereafter, without adjusting the hardness, the material was tempered at a standard heating temperature for a standard holding time, and then air-cooled to obtain a tempered material of the comparative example.
[0110] The quenching and tempering conditions of the comparative example are shown in Figure 8. In the comparative example, the quenching process involved holding the steel at 850°C for 120 minutes, followed by oil cooling. Then, in the tempering process, the steel was heated to 650°C, held for 300 minutes, and then air-cooled. Note that in the quenching and tempering processes of the comparative example, the holding time in the heated state was set longer than in the example of the invention in which a continuous furnace was used, so that the temperature of the steel would be uniform.
[0111] [Evaluation of hardness of tempered material (evaluation of variation at different positions in a continuous furnace)] Tempering was performed under the conditions of the above comparative example, and one piece of tempered material was taken from each of three locations in the batch furnace. The Rockwell hardness was measured on the axial measurement surface represented by surface S2 shown in Figure 5 and on radial measurement positions represented by measurement points P0 to P4. The three comparative tempered materials were designated as tempered materials No. 2-1, 2-2, and 2-3, and the hardness measurement results thereof are shown in Table 5 below.
[0112] [Table 5]
[0113] (Surface removal process) Then, a region of about 1.0 mm thickness was removed from the surface of the refined material to obtain a raw material. As a result, the diameter of the raw material was reduced by 2 mm compared to the diameter of the refined material. Note that, although the surface removal step was performed in this example, as described in the first and second embodiments, the surface removal step can be omitted depending on the state of the raw material.
[0114] (Plastic working process) Thereafter, each of the tempered materials was subjected to in-feed rolling to obtain a rolled material.
[0115] (High frequency hardening process) Thereafter, each of the obtained rolled materials was subjected to induction hardening to form a hardened layer on the surface, thereby obtaining a ball screw shaft.
[0116] [Evaluation of ball screw shaft accuracy] The thread accuracy was measured by calculating the cumulative pitch error for ball screw shaft No. 1 and ball screw shaft No. 2, which were manufactured using tempered material No. 1-1 and tempered material No. 2-1. The cumulative pitch error was calculated by measuring the distance between adjacent grooves for each ball screw shaft, which has an effective thread length of 72 mm and 18 grooves, and accumulating the difference in the distance between adjacent grooves. Note that the grooves at both ends of the ball screw shaft were excluded. The measurement results are shown in Table 6 below. In Table 6, the groove numbers are numbers assigned in sequence starting with groove number 1 for the groove at one end of the effective thread length toward the other end. Micrographs of the metal structure of ball screw shaft No. 1 after induction hardening are shown in Figures 9 and 10. Note that Figure 9 is a photograph of a cross section parallel to the shaft, and Figure 10 is a photograph of a cross section perpendicular to the shaft.
[0117] [Table 6]
[0118] As shown in Table 1 above, among the tempered materials obtained by the tempering method of the present invention, the one with the largest variation was tempered material No. 1-3, where the difference between the maximum and minimum hardness values on surface S2 was 0.7 (HRC). On the other hand, as shown in Table 5 above, among the tempered materials obtained by the tempering method of the comparative example, the one with the largest variation was tempered material No. 2-1, and the difference between the maximum and minimum hardness values on surface S2 was 4.0 (HRC). From these results, in the comparative example, the difference between the maximum and minimum hardness values was 4.0 (HRC), while in the invention example it was 0.7 (HRC). According to the present invention, the variation in hardness of the tempered material was reduced by 82.5%.
[0119] In addition, for the three tempered materials (tempered materials No. 1-4 to 1-6) that are examples of the present invention, the difference between the maximum and minimum hardness values at five axial measurement positions (P0 to P4) on the three axial measurement surfaces (S1 to S3) was confirmed. As a result, as shown in Tables 2 to 4, the tempered material No. 1-4 had the greatest hardness variation within one tempered material, but the difference between the maximum and minimum values was 2.2 (HRC), which was significantly below the range specified in the present invention (6 (HRC) or less).
[0120] In addition, referring to tempered material No. 1-4 shown in Table 2, the maximum difference between the maximum and minimum values on the same surface is 2.0 (HRC) on surface S1, and the minimum difference between the maximum and minimum values on the same surface is 0.8 (HRC) on surface S2, so 2.0 / 0.8=2.5 indicates that the variation within one tempered material is 2.5 times that of one surface. Here, for tempered materials No. 2-1 to 2-3, which are comparative examples shown in Table 5, the hardness was not measured at all points within one tempered material, but for example, in tempered material No. 2-1, the difference between the maximum and minimum hardness values was 4.0 (HRC), so the variation within one tempered material is considered to be about 2.5 times, or about 10 (HRC). From this result, it is understood that the variation in hardness of the tempered material obtained by the tempering method of the present invention is significantly smaller than that of the comparative example.
[0121] Furthermore, the metal structures of the tempered materials obtained by the tempering method of the present invention and the comparative tempered materials were observed under a microscope, and as a result, a uniform sorbite structure was observed overall in tempered materials Nos. 1-1 to 1-6. In contrast, tempered materials Nos. 2-1 to 2-3 had a sorbite structure overall, but a non-uniform appearance was observed.
[0122] Furthermore, when the cumulative pitch error of ball screw shaft No. 1, which is an example of the invention, was compared with that of ball screw shaft No. 2, which is a comparative example, as shown in Table 6, the cumulative pitch error of ball screw shaft No. 1 was 6 μm, which was a reduction of approximately 63% compared to the cumulative pitch error of ball screw shaft No. 2, which was 16 μm. As described above, if the target value for the grade of screw accuracy is, for example, between Ct7 and Ct8, the allowable displacement is 18 μm, which is also allowable for ball screw shaft No. 2 of the comparative example. However, ball screw shaft No. 1, which was manufactured by the manufacturing method of the present invention and had a cumulative pitch error of 6 μm, had extremely high accuracy compared to ball screw shaft No. 2 of the comparative example.
[0123] For reference, the cumulative pitch error was compared between the rolled material after the plastic processing process (before the induction hardening process) using the thermal refining method of the present invention and the ball screw shaft after the induction hardening process. As a result, the cumulative pitch error of the rolled material before the induction hardening process was 7 μm, and the cumulative pitch error of the ball screw shaft after the induction hardening process was 11 μm. Thus, although the lead cumulative pitch error increased slightly due to the induction hardening process, stable accuracy could be maintained even after induction hardening was performed.
[0124] As shown in Fig. 9, the metal structure of the obtained ball screw shaft No. 1 had a hardened layer formed on the surface by induction hardening and had a uniform martensite single phase structure. In the cross section parallel to the axis in the core region, metal fibers extending in the direction along the rolling direction that occurred when the material steel was formed and a uniform sorbite structure could be observed. Furthermore, in the boundary layer between the core region and the hardened layer, a mixture of sorbite and martensite structures could be observed. Furthermore, as shown in Figure 10, in the cross section perpendicular to the axis in the core region, no metal fibers extending in the rolling direction were observed, and it was confirmed that a uniform sorbite structure remained even after the high-frequency hardening process.
[0125] As described above, the present specification discloses the following: (1) In a mechanical structural component in which grooves and teeth are formed by plastic processing, a hardened layer having a martensite structure formed on the surface by induction hardening; a core region having a sorbite structure; A boundary layer having a mixture of a sorbite structure and a martensite structure formed between the core region and the hardened layer, A machine structural member, characterized in that the core region has a Rockwell hardness of 13 to 28 (HRC), and the variation in the Rockwell hardness is within 6 (HRC). This configuration makes it possible to obtain high accuracy and excellent quality.
[0126] (2) A mechanical structural component as described in (1), characterized in that the grooves and teeth are formed by infeed rolling. According to this configuration, the machining accuracy of the grooves can be improved.
[0127] (3) A machine structural member according to (1) or (2), characterized in that it is one selected from a screw shaft, a rack, a gear, and a serration. According to this configuration, the machining accuracy can be further improved, particularly in the screw shaft, rack, gears, and serrations.
[0128] (4) The variation in Rockwell hardness represents the difference between the maximum value and the minimum value when the Rockwell hardness is measured at any multiple different measurement points in the core region, The difference between the maximum value and the minimum value is within 6 (HRC), The machine structural member according to any one of (1) to (3), wherein the maximum value and the minimum value are both within a range of 13 to 28 (HRC). This configuration makes it possible to obtain even higher accuracy and superior quality.
[0129] (5) A ball screw shaft in which a screw groove is formed by infeed rolling, The variation in Rockwell hardness represents a difference between a maximum value and a minimum value when comparing Rockwell hardness at measurement positions in the same plane perpendicular to the longitudinal direction of the core region and the entire core region, The length of the ball screw shaft in the longitudinal direction is L, Three planes perpendicular to the longitudinal direction at a position spaced a predetermined distance from one end of the longitudinal direction are set as axial direction measurement planes, The axial measurement surface is set to one surface at a position selected within a range of 0.05L to 0.20L away from one end in the longitudinal direction, one surface at a position selected within a range of 0.45L to 0.55L away from one end in the longitudinal direction, and one surface at a position selected within a range of 0.80L to 0.95L away from one end in the longitudinal direction, The distance from the radial center of the ball screw shaft to the outer diameter of the shaft is defined as r, When the center of the ball screw shaft and four points selected at approximately equal intervals on a circumference spaced 0.5r apart from the center in the radial direction are set as radial measurement positions, The comparison within the same plane is a comparison of Rockwell hardness at five radial measurement positions, The comparison of the Rockwell hardness at the measurement positions throughout the core region is a comparison of the Rockwell hardness at the five radial measurement positions on the three axial measurement surfaces; The difference between the maximum and minimum Rockwell hardness values on the same surface is 2 (HRC) or less, The difference between the maximum and minimum Rockwell hardness values at the five radial measurement positions on the three axial measurement surfaces is 6 (HRC) or less; The mechanical structural component described in (1), characterized in that the maximum and minimum Rockwell hardness values at the five radial measurement positions on the three axial measurement surfaces are all within the range of 13 to 28 (HRC). According to this configuration, the thread accuracy of the ball screw shaft can be improved.
[0130] (6) A method for producing a mechanical structural member according to any one of (1) to (5), comprising the steps of: A tempering process of tempering a steel material to obtain a tempered material having a sorbite structure, a Rockwell hardness of 13 to 28 (HRC) in a material portion excluding a predetermined thickness from the surface, and a variation in the Rockwell hardness of the material portion within 6 (HRC); a plastic processing step of performing plastic processing on a surface of the tempered material on which the grooves and teeth are formed to obtain a processed material; a high-frequency hardening step of performing high-frequency hardening on the processed material; A manufacturing method for a machine structural member, comprising: According to this configuration, the productivity is excellent, the manufacturing costs can be reduced, and machine structural members having high precision and excellent quality can be manufactured.
[0131] (7) A method for manufacturing a mechanical structural member according to (6), characterized in that neither annealing nor tempering is carried out between the tempering step and the plastic processing step. According to this configuration, it is possible to further improve the productivity and reduce the manufacturing costs.
[0132] (8) A method for manufacturing a mechanical structural component according to (6) or (7), characterized in that the plastic processing is an in-feed rolling process.
[0133] (9) The tempering step comprises: a quenching step of heating and then cooling the material steel; A tempering process in which the steel material after the quenching process is heated and cooled to form a sorbite structure, The heating temperature and holding time in the quenching process are adjusted so that the material steel after the quenching process has a martensite single phase structure, The method for manufacturing a mechanical structural component according to any one of (6) to (8), characterized in that in the tempering process, the heating temperature for the tempering is adjusted so that the Rockwell hardness of the material portion is 13 to 28 (HRC) based on the relationship between the tempering temperature and hardness specific to the material steel. According to this configuration, the productivity is further improved, the manufacturing costs can be reduced, and machine structural members having high precision and excellent quality can be manufactured.
[0134] (10) Before the tempering step, a quenching test process for performing quenching using a test material having substantially the same shape and composition as the material steel, observing the structure of the test material after quenching, and selecting quenching heating conditions in which the structure becomes a martensite single phase structure; The method for manufacturing a machine structural member according to any one of (6) to (9), characterized in that the quenching step is carried out using the quenching heating conditions selected in the quenching test step. According to this configuration, the productivity is further improved, the manufacturing costs can be reduced, and machine structural members having high precision and excellent quality can be manufactured.
[0135] (11) Between the quenching test process and the tempering process, A tempering test process includes tempering the test material after the quenching test process at a heating temperature selected based on the relationship between the tempering temperature and hardness specific to the material steel, and selecting tempering heating conditions such that the test material becomes a sorbite structure, the Rockwell hardness of the material part of the test material is 13 to 28 (HRC), and the variation in Rockwell hardness of the material part of the test material is within 6 (HRC), The manufacturing method of a mechanical structural member according to (10), characterized in that the tempering step is carried out using the tempering heating conditions selected in the tempering test step. According to this configuration, the productivity is further improved, the manufacturing costs can be reduced, and machine structural members having high precision and excellent quality can be manufactured.
[0136] (12) Before the quenching step, After performing quenching using a tempered test material having substantially the same shape and composition as the material steel, a tempering test step of tempering the tempered test material at a heating temperature selected based on a relationship between the tempering temperature and hardness specific to the material steel, The tempering test step is a step of selecting quenching heating conditions and tempering heating conditions so that the tempered test material has a sorbite structure, the Rockwell hardness of the material portion is 13 to 28 (HRC), and the variation in Rockwell hardness of the material portion is within 6 (HRC), The quenching step is carried out using the quenching heating conditions selected in the thermal refining test step, The manufacturing method of a mechanical structural member according to (9), characterized in that the tempering process is carried out using the tempering heating conditions selected in the thermal refining test process. According to this configuration, the quenching heating conditions and the tempering heating conditions can be determined without conducting a test for determining only the quenching conditions.
[0137] Although various embodiments have been described above, it goes without saying that the present invention is not limited to such examples. It is clear that a person skilled in the art can come up with various modified or revised examples within the scope of the claims, and it is understood that these also naturally belong to the technical scope of the present invention. Furthermore, the components in the above-mentioned embodiments may be arbitrarily combined within the scope of the invention.
[0138] This application is based on a Japanese patent application (Patent Application No. 2022-077203) filed on May 9, 2022, the contents of which are incorporated by reference into this application. [Explanation of symbols]
[0139] 1,2 Round bar material 11 Tempering section 12 Softening layer 13,14,31a Hardened layer 21 Test material 31 Ball screw shaft 31b Core area 31c boundary layer 32 Groove 33 teeth
Claims
1. In a machine structural member in which grooves and teeth are formed by plastic working, a hardened layer having a martensite structure formed on the surface by induction hardening; a core region having a sorbite structure; A boundary layer having a mixture of a sorbite structure and a martensite structure formed between the core region and the hardened layer, A machine structural member, characterized in that the Rockwell hardness in the core region is 13 to 28 (HRC), and the variation in the Rockwell hardness is within 6 (HRC).
2. 2. The mechanical structural member according to claim 1, wherein the grooves and teeth are formed by infeed rolling.
3. 2. The machine structural member according to claim 1, which is one selected from the group consisting of a screw shaft, a rack, a gear and a serration.
4. The variation in Rockwell hardness represents a difference between a maximum value and a minimum value when Rockwell hardness is measured at a plurality of arbitrary different measurement points in the core region, The difference between the maximum value and the minimum value is within 6 (HRC), 2. The mechanical structural member according to claim 1, wherein the maximum value and the minimum value are both within a range of 13 to 28 (HRC).
5. A ball screw shaft with a screw groove formed by infeed rolling. The variation in Rockwell hardness represents a difference between a maximum value and a minimum value when comparing Rockwell hardness at measurement positions in the same plane perpendicular to the longitudinal direction of the core region and the entire core region, The length of the ball screw shaft in the longitudinal direction is L, Three planes perpendicular to the longitudinal direction at a position spaced a predetermined distance from one end of the longitudinal direction are set as axial direction measurement planes, The axial measurement surface is set to one surface at a position selected within a range of 0.05L to 0.20L from one end in the longitudinal direction, one surface at a position selected within a range of 0.45L to 0.55L from one end in the longitudinal direction, and one surface at a position selected within a range of 0.80L to 0.95L from one end in the longitudinal direction, The distance from the radial center of the ball screw shaft to the outer diameter of the shaft is defined as r, When the center of the ball screw shaft and four points selected at approximately equal intervals on a circumference spaced 0.5r from the center in the radial direction are set as radial measurement positions, The comparison within the same plane is a comparison of Rockwell hardness at five radial measurement positions, The comparison of the Rockwell hardness at the measurement positions throughout the core region is a comparison of the Rockwell hardness at the five radial measurement positions on the three axial measurement surfaces; The difference between the maximum and minimum Rockwell hardness values in the same plane is 2 (HRC) or less. a difference between a maximum value and a minimum value of Rockwell hardness at the five radial measurement positions on the three axial measurement surfaces is 6 (HRC) or less; 2. The mechanical structural member according to claim 1, wherein the maximum and minimum Rockwell hardness values at the five radial measurement positions on the three axial measurement surfaces are all within a range of 13 to 28 (HRC).
6. A method for manufacturing a mechanical structural member according to any one of claims 1 to 5, comprising the steps of: a tempering process for tempering a steel material to obtain a tempered material having a sorbite structure, a Rockwell hardness of 13 to 28 (HRC) in a material portion excluding a predetermined thickness from the surface, and a variation in the Rockwell hardness of the material portion of 6 (HRC) or less; a plastic processing step of performing plastic processing on a surface of the tempered material on which the grooves and teeth are formed to obtain a processed material; a high-frequency hardening step of performing high-frequency hardening on the processed material; A manufacturing method for a machine structural member, comprising:
7. The method for manufacturing a machine structural member according to claim 6, wherein neither annealing nor hardening is carried out between the thermal refining step and the plastic working step.
8. The method for manufacturing a machine structural member according to claim 6, wherein the plastic working is an in-feed rolling process.
9. The tempering step includes: a quenching step of heating and then cooling the material steel; A tempering process in which the steel material after the quenching process is heated and cooled to form a sorbite structure, The heating temperature and holding time in the quenching process are adjusted so that the material steel after the quenching process has a martensite single phase structure, 7. The method for manufacturing a mechanical structural member according to claim 6, characterized in that in the tempering process, a heating temperature for the tempering is adjusted so that the material portion has a Rockwell hardness of 13 to 28 (HRC) based on a relationship between the tempering temperature and hardness specific to the material steel.
10. Before the tempering step, a quenching test process for performing quenching using a test material having substantially the same shape and composition as the material steel, observing the structure of the test material after quenching, and selecting quenching heating conditions in which the structure becomes a martensite single phase structure; 7. The method for manufacturing a machine structural member according to claim 6, wherein the hardening step is carried out using the hardening heating conditions selected in the hardening test step.
11. Between the quenching test step and the tempering step, a tempering test process for selecting tempering heating conditions under which the test material after the quenching test process is tempered at a heating temperature selected based on a relationship between the tempering temperature and hardness specific to the material steel, the test material becomes a sorbite structure, the Rockwell hardness of the material part of the test material is 13 to 28 (HRC), and the variation in Rockwell hardness of the material part of the test material is within 6 (HRC); The method for manufacturing a machine structural member according to claim 9, wherein the tempering step is carried out using the tempering heating conditions selected in the tempering test step.
12. Prior to the quenching step, After performing quenching using a tempered test material having substantially the same shape and composition as the material steel, a tempering test step of tempering the tempered test material at a heating temperature selected based on a relationship between the tempering temperature and hardness specific to the material steel, The thermal refining test step is a step of selecting quenching heating conditions and tempering heating conditions so that the thermal refining test material after the tempering has a sorbite structure, the Rockwell hardness of the material portion is 13 to 28 (HRC), and the variation in Rockwell hardness of the material portion is within 6 (HRC), The quenching step is carried out using the quenching heating conditions selected in the thermal refining test step, 9. The method for manufacturing a machine structural member according to claim 8, wherein the tempering step is carried out using the tempering heating conditions selected in the thermal refining test step.
Citation Information
Patent Citations
Ball screw shaft and manufacturing method therefor
JP2003119518A
Screw shaft and method for manufacturing the same
JP2013092212A
Method of manufacturing screw shaft of ball screw, and ball screw
JP2015042897A